Pengenalan Karakteristik Bullying dalam Tindak Pidana Melalui Media Antic (Anti Bullying Cards) bagi Guru dan Orang Tua - Agung Aditya; Ariesma Setyarum; Hanindya Restu Aulia; Dina Nurmalisa; Afrinar Pramitasari; Desyarini Puspita Dewi (Universitas Kristen Indonesia Toraja, 2024)
This study aims to introduce the characteristics of bullying as a criminal act through Antic (Anti-Bullying Cards) as an educational medium for teachers and parents. Bullying is a form of violent behavior that can have negative impacts on victims, especially among children and adolescents. Although bullying frequently occurs in schools and homes, public understanding—particularly among teachers and parents—regarding its legal aspects remains limited. Therefore, this study develops Antic as an educational tool to help teachers and parents identify the signs and effects of bullying while providing insights into its legal implications. The medium is designed as interactive cards containing information on the definition of bullying, its various types, and preventive measures. This approach is expected to raise awareness and enhance the knowledge of teachers and parents about their crucial roles in preventing and addressing bullying, thereby fostering a safer environment for children. The study employs a research-based media development method, incorporating product trials with teachers and parents to gather feedback for further refinement of the medium